2021
DOI: 10.1007/s10689-021-00240-6
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and psychosocial impact of genetic counseling and multigene panel testing among individuals with ovarian cancer

Abstract: In a sample of individuals with ovarian cancer, we aimed to (a) identify factors associated with the psychosocial impact of genetic counseling and multigene panel testing, (b) identify factors associated with cancer genetics knowledge, and (c) summarize patient-reported recommendations to improve the genetic counseling and multigene panel testing process. Eligible participants in this secondary analysis of quantitative and qualitative survey data were English-speaking adults with ovarian cancer. Psychosocial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
4
1
Order By: Relevance
“…In contrast to cancer-related distress, a significant reduction in genetic testing-related distress was noted from disclosure of research, establishing relevant cut-offs for this tool is an important area for further study. Of note, despite decreases in the average MICRA scores among our cohort, scores remained higher than those previously published among individuals with ovarian cancer following germline genetic testing (mean MICRA scores: 17.7-20) (Bjornslett et al, 2015;Pozzar et al, 2022;Richardson et al, 2020).…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…In contrast to cancer-related distress, a significant reduction in genetic testing-related distress was noted from disclosure of research, establishing relevant cut-offs for this tool is an important area for further study. Of note, despite decreases in the average MICRA scores among our cohort, scores remained higher than those previously published among individuals with ovarian cancer following germline genetic testing (mean MICRA scores: 17.7-20) (Bjornslett et al, 2015;Pozzar et al, 2022;Richardson et al, 2020).…”
Section: Discussioncontrasting
confidence: 81%
“…They are also more likely to have young children, which could contribute to initial uncertainty and genetic testing‐related distress. It is not surprising that individuals in our cohort who received only negative genetic testing results had lower levels of genetic testing‐related distress, as receiving a positive genetic test result is associated with increased genetic testing‐related distress (Bjornslett et al, 2015; Pozzar et al, 2022; Richardson et al, 2020). While the number of individuals in this study is too small to make meaningful conclusions, it is interesting to note that individuals who received positive tumor and negative germline results had a very large reduction in genetic testing‐related distress from disclosure of tumor to germline results.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…While the increased complexity and uncertainty associated with multigene testing could adversely impact patient responses to genetic counseling, initial studies on outcomes of multigene counseling and testing have reported comparable outcomes to traditional single gene counseling and testing. [34][35][36] The expansion of genetic referral guidelines and concomitant increased demand, have fostered alternative approaches to pre-test genetic counseling. 37 While our study incorporated telephonebased genetic counseling, the impact of more recent technologybased approaches (e.g., chatbots), physician-delivered counseling, and post-test only counseling remain to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Multigene genetic counseling must also address the increased likelihood of detecting a variant of uncertain clinical significance. While the increased complexity and uncertainty associated with multigene testing could adversely impact patient responses to genetic counseling, initial studies on outcomes of multigene counseling and testing have reported comparable outcomes to traditional single gene counseling and testing 34‐36 …”
Section: Discussionmentioning
confidence: 99%